Speech-in-noise perception in high-functioning individuals with autism or Asperger's syndrome - Alcántara, José I.; Weisblatt, Emma J.L.; Moore, Brian C.J.; Bolton, Patrick F. (Journal of child psychology and psychiatry, 2004)
Background:  High‐functioning individuals with autism (HFA) or Asperger's syndrome (AS) commonly report difficulties understanding speech in situations where there is background speech or noise. The objective of this study was threefold: (1) to verify the validity of these reports; (2) to quantify the difficulties experienced; and (3) to propose possible mechanisms to explain the perceptual deficits described. Method:  Speech‐in‐noise perception abilities were measured using speech reception thresholds (SRTs), defined as the speech‐to‐noise ratio (SNR) at which approximately 50% of the speech is correctly identified. SRTs were measured for 11 individuals with HFA/AS and 9 age/IQ‐matched normal‐hearing control subjects, using an adaptive procedure, in a non‐reverberant sound‐attenuating chamber. The speech materials were standardised lists of everyday sentences spoken by a British male speaker. The background sounds were: (1) a single female talker; (2) a steady speech‐shaped noise; (3) a speech‐shaped noise with temporal dips; (4) a steady speech‐shaped noise with regularly spaced spectral dips; and (5) a speech‐shaped noise with temporal and spectral dips. Results:  SRTs for the HFA/AS group were generally higher (worse) than those for the controls, across the five background sounds. A statistically significant difference in SRTs between the subject groups was found only for those background sounds that contained temporal or spectro‐temporal dips. SRTs for the HFA/AS individuals were 2 to 3.5 dB higher than for the controls, equivalent to a substantial decrease in speech recognition. Expressed another way, the HFA/AS individuals required a higher SNR, whenever there were temporal dips in the background sound, to perform at the same level as the controls. Conclusions:  The results suggest that the speech‐in‐noise perception difficulties experienced by individuals with autism may be due, in part, to a reduced ability to integrate information from glimpses present in the temporal dips in the noise.